Construction and Comparison of ceRNA Regulatory Network for Different Age Female Breast Cancer - Liu, Zhi-Qin; Zhang, Gao-Tao; Jiang, Li; Li, Chun-Qing; Chen, Que-Ting; Luo, Du-Qiang (Frontiers in Genetics, 2021)
Studies have shown the difference appearing among the prognosis of patients in different age groups. However, the molecular mechanism implicated in this disparity have not been elaborated. In this study, expression profiles of female BRCA associated mRNAs, lncRNAs and miRNAs were downloaded from the TCGA database. The sample were manually classified into 3 groups according to their age at initial pathological diagnosis: young (age ≤39 years), elderly (age ≥65 years), and intermediate (age 40-64 years). lncRNA-miRNA-mRNA ceRNA network was respectively constructed for different age BRCA. Then, the biological functions of the DEmRNAs in ceRNA network were further investigated by Gene Ontology (GO) and Kyoto Encyclopedia of Genes and Genomes (KEGG) pathway analysis. Finally, survival analysis was used to identify prognostic biomarkers for different age BRCA patients. We identified 13 RNAs, 38 RNAs and 40 RNAs specific to patients aged≤39 years，aged 40-64 years, and aged ≥65 years, respectively. Furthermore, the unique pathways were mainly enriched in cytokine-cytokine receptor interaction in patients aged 40-64 years, and were mainly enriched in TGF-beta signaling pathway in patients aged ≥65 years. According to the overall survival analysis, 1 lncRNA, 7 RNAs and 10 RNAs were respectively functioned as prognostic biomarkers in young, intermediate and elderly group. In summary, our study identified the differences in the ceRNA regulatory networks and provides an effective bioinformatics basis for further understanding of the pathogenesis and predicting outcomes for different age BRCA.